The University of Nonstop Society: Campus Planning, Lounge Space, and Incessant Productivity. Issue 1 (2nd January 2021) - Austin, Samuel; Sharr, Adam
Abstract: The University of Birmingham, UK, has been at the forefront of the last decade's marketization of higher education in England. It has invested massively in its estate, and we examine the ideologies at work in its new masterplan and architecture. We account for the campus's history. We then review the idea of lounge space – around which it has been reconfigured – and focus on three projects: The Alan Walters Building, a new Library, and the so-called Green Heart. We examine the ideological outlook of the campus and its new architecture to draw conclusions about the ideas of contemporary society and economy that they represent. The trajectory of its masterplanning and architecture inscribe a shift from a postwar liberal view of higher education to a contemporary marketized one under the economic, social and cultural condition characterized as neoliberalism. It now constitutes what we call the university of nonstop society.